Edukasi Dan Simulasi Senam Tera Untuk Pencegahan Hipertensi Pada Lansia Di Desa Nguri Kecamatan Lembeyan Kabupaten Magetan - Devita Anugrah Anggraini; Mega Arianti Putri; Didit Damayanti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
As a person ages, various changes often arise due to a decrease in biological function caused by the aging process. Hypertension is one of the NCDs that is a threat, especially to the elderly. Based on data from the World Health Organization (WHO) in 2019, it shows that around 1.13 million people in the world experience hypertension. Nguri Village is one of the villages in Lembeyan District, Magetan Regency, East Java Province. The problem from the results of the study in Nguri Village is that there are still many people, especially the elderly, who suffer from hypertension and a lack of understanding in preventing hypertension, namely 75% or 45 out of 60 elderly people. The aim of community service is to increase knowledge regarding efforts to prevent hypertension. The implementation method uses health education in the form of doing tera exercises to prevent hypertension in the elderly. Previously, blood pressure was measured. Activities were carried out on 30 hypertensive elderly aged >40 years. The results of the activity were that the elderly knew about preventing hypertension, namely 95% of the 30 elderly were able to understand and the elderly were able to carry out tera and exercise activities. The elderly play a very active role in this activity.